Learning content versus social environment. A comparative analysis from traditional initiation and modern high-schooling in Java (Indonesia) - Jean-Marc de Grave; Puji Yanti Fauziah (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2019)
The circulation of contents depends on the marked separation of social domains and sub-domains: they are transformed from one domain to another (from the scientific milieu to the media or the school environment, for example). A competition of domains is thus developed, which aims to enhance the radiance of contents reflecting knowledge some of which dominate, others not, others are ignored or unrecognised and still others disappear. Finally, the description of Indonesian high schools presents modes of transmission that do not overvalue the learning content to the detriment of relationship established between the different members of some of these high schools. The two first high schools I have described (SMA3 and de Britto), present in their internal operating mode of transmission the same configuration as the nyantri system found in traditional kanuragan insofar as it shows how it is very difficult, if not impossible, to separate a so-called learning content from a learning community and a social environment. From these two examples we can understand that socialising ability is all the same educable and transmissible in a high formal context, and that the positive integration of the relation to time, space and others clearly adds that of the relation to knowledge.